Effect of valsartan on kidney outcomes in people with impaired glucose tolerance. Issue 6 (17th March 2017) - Currie, Gemma; Bethel, M. Angelyn; Holzhauer, Björn; Haffner, Steven M.; Holman, Rury R.; McMurray, John J. V.
Abstract : Aims: To examine the effect of valsartan on kidney outcomes in patients with impaired glucose tolerance (IGT). Methods: In a double‐blind randomized trial, 9306 patients with IGT were assigned to valsartan (160 mg daily) or placebo. The co‐primary endpoints were the development of diabetes and two composite cardiovascular outcomes. Prespecified renal endpoints included: the composite of renal death, end‐stage renal disease (ESRD) or doubling of serum creatinine; estimated glomerular filtration rate (eGFR) ≤30 mL/min/1.73 m 2 ; hospitalization for renal failure; and progression from normoalbuminuria to microalbuminuria, microalbuminuria to macroalbuminuria, and normoalbuminuria to macroalbuminuria. The median follow‐up was 6.2 years. Results: Valsartan reduced the incidence of diabetes but not cardiovascular events. In the valsartan group, 25/4631 patients (0.5%), vs 26/4675 (0.6%) patients in the placebo group, developed ESRD or experienced doubling of serum creatinine (hazard ratio [HR] 0.96, 95% confidence interval [CI] 0.55‐1.66; P  = .87). Few patients in either group developed an eGFR of ≤30 mL/min/1.73 m 2 or had a renal hospitalization. Fewer patients on valsartan (237/4084 [5.8%]) than on placebo (342/4092 [8.4%]) developed microalbuminuria (HR 0.68, 95% CI 0.57‐0.80; P  < .0001), and fewer valsartan‐treated patients developed macroalbuminuria. Overall, urinary albumin‐to‐creatinine ratio (UACR) was 11% lower with valsartan (95% CI 8‐13; P  < .0001) and 9% lower (95% CI 6‐11; P  < .0001) after adjusting for both glucose and blood pressure. Conclusions: The effect of valsartan on UACR was not wholly explained by change in blood pressure or glucose. Valsartan reduced the incidence of microalbuminuria in IGT without increasing the incidence of hyperkalaemia or renal dysfunction compared with placebo.